Anxiety and depression in relation to body mass index - Jat, Muhammad Ilyas; Washdev, Washdev; Saleem, Farah; Sarwar, Ayesha; Wadhwani, Anil; Ahmed, Shoaib (Journal of Pakistan Psychiatric Society, 2020)
Objective: To determine the frequency of Anxiety and Depression in relation to Body Mass Index among clients reporting to a Tertiary Care Hospital at Malir Karachi. Design: A cross-sectional study. Place and Duration: Outpatient Department (OPD), Department of Medicine and allied, Al-Tibri Medical College and Hospital, Malir, Karachi, from 10th April 2017 to 9th October 2017. Patients and Methods: Total 100 cases of both genders were enrolled in the study. Anxiety and Depression were assessed by Hospital Anxiety and Depression scale. The data was analyzed on SPSS version 20.0. Results: All enrolled cases with average age 50.35 ± 8.85, having 39% males and 61% females. Amongst all 63% were married while 37% were single. Among total, 19% were having BMI between 20-24.9 kg/m2, 38% were overweight having BMI 25-28.9 kg/m2 and 43% were Obese having BMI greater than 29 kg/m2. Anxiety was assessed through Hospital Anxiety and Depression Scale was found to be 23% normal, 43% borderline and 34% were abnormal for anxiety. Depression as assessed by Hospital Anxiety and Depression Scale was 29% were normal, 33% were borderline and 38% were abnormal for depression. Conclusion: From this study, it is concluded that although Anxiety and Depression are prevalent among clients of high Body Mass Index but statistically not significantly associated.